Sustainable rural bioenergy production for developing countries. Issue 24 (16th December 2016) - Demirbas, Ayhan; Demirbas, Burak
ABSTRACT: Bioenergy is a renewable energy source made from biomass, which are organic materials such as plants and animals. Until enough biomass resources to ensure energy demand in the world is available, the bioenergy obtained from biomass, there may be used for heat, electrical and transport. Main biomass thermo-chemical conversion technologies are pyrolysis, gasification, and liquefaction. Biomass can be burned to produce heat and electricity, changed to gas-like fuels such as methane, hydrogen, and carbon monoxide, or changed to a liquid fuel. Modern biomass can be used for the generation of electricity and heat using modern conversion technologies. Technological advances have made modern biomass cogeneration plants cleaner, more efficient, and, under certain conditions, cost-effective as compared to public utility grids and fossil-fuel boilers or generators. Biomass can be converted to liquid biofuels: bioethanol and biodiesel. Two biofuels are becoming more and more attractive and competitive as complementary to or substitutions for petroleum basic products, due to their economic and environmental benefits.